Scientific studies of V.О. Kudashev on the Preservation of moisture in the soil at the Kiriakov test field (1878–1888) - Stolyar, O. P. (History of science and technology, 2018)
The scientific contribution of рrince V.O. Kudashev on soil moisture preservation, determination aimed at optimizing the physical parameters of the soil, for obtaining the stable harvests of winter crops in conditions of insufficient moisture. A specific plan for agro-measures applying was proposed by V.O. Kudashev and it is predicted an optimizing the physical parameters of the soil, to obtain sustainable winter crops in conditions of insufficient moisture. He noticed that it is not necessary to loose the soil until dry weather is established or the soil does not dry up to the possibility of its loosening. He recommended not to defend after plowing, as well as during rooting it is necessary to do it deeper than the previous one and not use harrowing. When applying the last agro-measure, we should not pay attention to the intensive growth of weeds in fallow, because in years with high rainfall, they mitigate the harmful effects of excess rain on steam. Thus, on the one hand, the consolidation of soil from the rain was mechanically weakened, and this is not much: at 400 ml of precipitation – 300 thousand pounds per tithing; but on the other hand, the deposition of soil actually took place. It has been established that the best conditions for preserving soil moisture are achieved in the case of shallow, rather than deep cultivation of soil: in spite of the widespread opinion that softly cultivated soils, when adverse conditions occur, spend not only soil moisture but also a lot of useful soil substances; to better preserve and to accumulate more moisture, the early harvesting of soil in fallow is too important for obtaining a higher winter crop; black fallow are not the best way to prepare a field for sowing winter; The use of seedlings under winter conditions in summer fallow is associated with additional drying, and therefore can’t be promising for the Poltava province. The researcher warned against too early terms of winter sowing, arguing that overgrown plants can’t withstand the entire set of climatic problems in autumn, winter and especially early spring. He stressed that the same conditions, the same heat and moisture precisely contribute to the infinite reproduction of various plant parasitic organisms, which negatively affects the quantity and quality of crops. In addition, Prince V.O. Kudashev also found that to maintain soil moisture, all subsequent agrotechnical measures to treat the winter field for the sowing of winter plants subordinate to the principle of preservation of soil moisture, which means – with the restoration of the burrowing ground of the winter field of its capillary structure, new looseness to destroy the new capillaries of its upper layer, adjusting the onset of the moment of ripeness of the soil to the day of sowing of seeds.